A Comparison between the Effects of Evening Primrose Oil and Soybean Oil on Menopause Symptoms - RM Aftan; MK Abdulridha; B Abd al-Jbori (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2023)
Background and Objective: More than 80% of women experience physical, vasomotor, sexual and psychological symptoms after menopause, and in 10-20% of women, the severity of menopause symptoms affects their quality of life. Due to the complications of using chemical drugs, this study was conducted to compare the effectiveness of evening primrose oil and soybean oil in postmenopausal women. Methods: In this randomized controlled prospective study, 40 postmenopausal women were assigned into two groups of 20, 500 mg of evening primrose oil and 233 mg of soybean oil extract twice a day for 8 weeks. Measurement of serum hormones (follicle stimulating hormone, luteinizing hormone, estradiol), lipid profile, fasting blood glucose, and high sensitivity C-reactive protein were performed. Moreover, menopausal symptoms were analyzed and compared based on the evaluation score of menopausal symptoms (range 0-3). Findings: The mean age of women was (51.65±3.7) years. After 2 months of treatment with evening primrose oil, there was a decrease in follicle stimulating hormone, luteinizing hormone levels concurred with increase in estradiol levels (-10.64%) (-8.09%) (7.47%), respectively (p<0.05). Meanwhile, women receiving the soybean oil revealed increase in all the three hormones (5.77%) (12.73%) (13.39%), respectively (p<0.05). Total cholesterol and triglycerides decreased in both study groups after treatment (p<0.05), fasting blood glucose level decreased in group 1 only (-1.39%), and high sensitivity C-reactive protein decreased in group 2 only (-22.33%) (p<0.05). In both groups, women presented with mild to moderate pre-treatment menopausal symptoms (Menopause Symptom Assessment score ranging from 0.75 to 2.25) showed significant decrease in their score up to no symptoms in each study group after 2 months (less than 0.75) (p<0.01)‎. Conclusion: The results of the study showed that both evening primrose oil and soybean oil supplements improve menopausal symptoms.